2021
DOI: 10.1371/journal.pntd.0009374
|View full text |Cite|
|
Sign up to set email alerts
|

DNA vaccination induced protective immunity against SARS CoV-2 infection in hamsterss

Abstract: The development of efficient vaccines against COVID-19 is an emergent need for global public health. The spike protein of severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2) is a major target for the COVID-19 vaccine. To quickly respond to the outbreak of the SARS-CoV-2 pandemic, a nucleic acid-based vaccine is a novel option, beyond the traditional inactivated virus vaccine or recombinant protein vaccine. Here, we report a DNA vaccine containing the spike gene for delivery via electroporation. The sp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
24
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 19 publications
(25 citation statements)
references
References 52 publications
1
24
0
Order By: Relevance
“…We have previously applied an EP device for use in animals to deliver the SARS-CoV-2 DNA vaccine, which has a protective effect against SARS-CoV-2 infection in hamsters 14 . A suitable delivery system to enhance DNA vaccine efficacy is required to bridge the gap between the development phase and clinical study.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…We have previously applied an EP device for use in animals to deliver the SARS-CoV-2 DNA vaccine, which has a protective effect against SARS-CoV-2 infection in hamsters 14 . A suitable delivery system to enhance DNA vaccine efficacy is required to bridge the gap between the development phase and clinical study.…”
Section: Resultsmentioning
confidence: 99%
“…Our previous studies showed that a DNA vaccine with the tumor-associated antigen L6 followed by EP could induce cellular immunity against cancer growth 13 . We further applied this approach for COVID-19, and the DNA-encoded full-length spike (S) protein of SARS-CoV-2 (pSARS2-S) was shown to induce protective immune responses against viral challenge in hamsters 14 . EP combined with DNA vaccination greatly increases the efficacy of DNA vaccines 3 5 .…”
Section: Introductionmentioning
confidence: 99%
“…In this work, we evaluated the protective efficacy of a pcDNA3.1 vectored SARS-CoV-2 spike antigen fused with and without CD40L in a SARS-CoV-2 Syrian hamster challenge model. It is noted in the literature that doses of DNA vaccines vary, ranging from 50 to 200 µg with or without the use of alternative DNA vaccine delivery methods (45)(46)(47). In this study, we employed a 100 µg dose, as our study was mainly intended to compare the vaccines with or without CD40 ligand.…”
Section: Discussionmentioning
confidence: 99%
“…Nevertheless, current plasmid DNA vaccines often rely on a kanamycin-based selection marker, which is not generally used to treat bacterial infection in human. Considering such pros and cons, a DNA vaccine for SARS-CoV-2 is being developed and tested in preclinical and clinical studies [ 70 ]. ZyCoV-D, developed by Ahmedabad (headquarter)-based Zydus Cadila, and approved by DCGI, India, is the first plasmid DNA vaccine for SARS-CoV-2 in humans, and is currently undergoing clinical trial (CTRI/2020/07/026352)./).…”
Section: Nature Of Vaccinesmentioning
confidence: 99%